2007
DOI: 10.1139/w06-141
|View full text |Cite
|
Sign up to set email alerts
|

Papaya shoot tip associated endophytic bacteria isolated from in vitro cultures and host–endophyte interaction in vitro and in vivo

Abstract: Fourteen distinct bacterial clones were isolated from surface-sterilized shoot tips (approximately 1 cm) of papaya (Carica papaya L. 'Surya') planted on Murashige and Skoog (MS)-based papaya culture medium (23/50 nos.) during the 2-4 week period following in vitro culturing. These isolates were ascribed to six Gram-negative genera, namely Pantoea (P. ananatis), Enterobacter (E. cloacae), Brevundimonas (B. aurantiaca), Sphingomonas, Methylobacterium (M. rhodesianum), and Agrobacterium (A. tumefaciens) or two Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 39 publications
2
46
0
3
Order By: Relevance
“…Moreover, previous studies reported that P. ananatis was isolated as an endophytic PGPR from ginseng, papaya, and maize Rijavec et al, 2007;Thomas et al, 2007). This study shows, for the first time, the successful treatment of pepper plants with newly identified P. ananatis B1-9 leading to an increased pepper fruit yield.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, previous studies reported that P. ananatis was isolated as an endophytic PGPR from ginseng, papaya, and maize Rijavec et al, 2007;Thomas et al, 2007). This study shows, for the first time, the successful treatment of pepper plants with newly identified P. ananatis B1-9 leading to an increased pepper fruit yield.…”
Section: Discussionmentioning
confidence: 55%
“…The third possible origin of the nonpathogenic clones whose RAPD patterns differ from those of the inoculated strain (option iii) is that they were present as endophytes in the inoculated plants or reached the plant from external sources, which is, in our opinion, the likeliest explanation. The occurrence of endophytic agrobacteria in otherwise healthy herbaceous and woody plants has been repeatedly shown by other authors (27,49,50,53,57). Conversely, it was reported that Agrobacterium populations apparently decline rapidly in water, although they can enter a viable but nonculturable state (26,46), and it is possible that they could recover from this state and colonize plants.…”
Section: Vol 75 2009 Virulence Of a Tumefaciens Strains From Tumormentioning
confidence: 60%
“…Although some studies have reported P. ananatis isolation from economically important crops, such as coffee (Nunes and de Melo, 2006), ginseng , papaya (Thomas et al, 2007), maize (Rijavec et al, 2007), and rice (Mano and Morisaki, 2008), they have failed to ascertain the essential growth parameters of this bacterium.…”
Section: Discussionmentioning
confidence: 99%